Subtypes of Blastocystis protozoa and clinical association in humans. - Sanprasert , V.; Nuchprayoon , S. (Chulalongkorn Medical Journal, 2023)
Blastocystis sp. is one of the most common intestinal protozoa of human and animals worldwide. Despite being first described in humans about 100 years ago, questions regarding the pathogenicity of Blastocystis sp. still remain unanswered. Blastocystis infections has increased in the last decade with public health significance. The infections can cause various gastrointestinal symptoms. Blastocystis sp. has been found in asymptomatic, acute symptomatic and chronic symptomatic individuals. Molecular techniques have revealed extensive genetic diversities of this protozoan. Until now, more than 17 subtypes have been reported. Subtypes 1- 9 have been reported in humans. However, the prevalence of each subtype is different in each country. The genetic diversity of the protozoa has led to the suggestion that the subtypes might be associated with a wide range of clinical symptoms. This article reviews an update of biology of Blastocystis sp. The distribution of Blastocystis subtypes in different countries and the associations between subtypes and clinical symptoms are discussed in details. The information about the associations with the clinical symptoms will contribute to a better understanding of Blastocystis pathogenicity in humans, useful for physicians to make treatment decision for the infection. Appropriate treatments of the infections can stop the transmission and prevent the drug resistance.